Lifetime and 12-month treatment for mental disorders and suicidal thoughts and behaviors among first year college students - Bruffaerts, R.; Mortier, P.; Auerbach, R.; Alonso, J.; Hermosillo De la Torre, A.; Cuijpers, P.; Demyttenaere, K.; Ebert, D.; Green, J.; Hasking, Penelope; Stein, D.; Ennis, E.; et al. (John Wiley & Sons, 2019)
© 2019 John Wiley & Sons, Ltd. Objectives: Mental disorders and suicidal thoughts and behaviors (STB) are common and burdensome among college students. Although available evidence suggests that only a small proportion of the students with these conditions receive treatment, broad-based data on patterns of treatment are lacking. The aim of this study is to examine the receipt of mental health treatment among college students cross-nationally. Methods: Web-based self-report surveys were obtained from 13,984 first year students from 19 colleges in eight countries across the world as part of the World Health Organization's World Mental Health–International College Student Initiative. The survey assessed lifetime and 12-month common mental disorders/STB and treatment of these conditions. Results: Lifetime and 12-month treatment rates were very low, with estimates of 25.3–36.3% for mental disorders and 29.5–36.1% for STB. Treatment was positively associated with STB severity. However, even among severe cases, lifetime and 12-month treatment rates were never higher than 60.0% and 45.1%, respectively. Conclusions: High unmet need for treatment of mental disorders and STB exists among college students. In order to resolve the problem of high unmet need, a reallocation of resources may focus on innovative, low-threshold, inexpensive, and scalable interventions.